Antropometri Rumoh Aceh di Kota Lhokseumawe - Hendra; Mirsa, Rinaldi; Saputra, Eri; Alashri, Haris; Ardyan, Muhammad (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
Rumoh Aceh is a lengthy process that extracts cultural values from the intelligence of the Acehnese people. In the past, the Acehnese people were unfamiliar with sophisticated tools for measuring dimensions, but they were familiar with the traditional measurement known as seunipat. The size of the body parts of the Rumoh Aceh owner serves as the benchmark, allowing for variations in the dimensions of the Rumoh Aceh column module. This study examines the application of anthropometry to Rumoh Aceh in the city of Lhokseumawe. The research methods applied are a mixture of qualitative and quantitative methods. The research sample technique uses purposive sampling. This study focuses on three Acehnese rumohs, who are over 50 years old and still exist in physical form. We collected the data through field observation and a review of relevant literature. The measurement data will be analyzed by converting the measurement results into unipat dimensions and comparing the three Aceh rumohs. The study's findings demonstrate variations in the use of anthropometry, as evidenced by the variations in the research sample's column module, which stem from variations in the homeowner's body dimensions.